CYTOTOXIC ACTIVITY AGAINST P-388 MURINE LEUKEMIA CELL FROM Lygodium microphyllum HERB - Hadi Kuncoro (Universitas Bhakti Kencana, 2016)
Lygodium microphyllum is an invasive climbing fern weed that has become aggressive in humid habitats in tropical regions. We studied its cytotoxic activity of methanol extract, n-hexane, Ethyl acetate, and n-butanol fraction. Various extract tested for cytotoxic activity on murine P388 leukemia cells using the MTT assay method. The results of the work indicated that IC50 values of methanol extract >100 Î¼g/mL, n-hexane fraction 62,186 Î¼g/mL, Ethyl acetate fraction 50,166 Î¼g/mL , and n-butanol fraction >100 Î¼g/mL on the growth of the P-388 murine leukemia cells.